Trade and the environment: The role of firm heterogeneity - Udo Kreickemeier; Philipp M. Richter (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper derives a new effect of trade liberalisation on the quality of the environment. We show that in the presence of heterogeneous firms the aggregate volume of emissions is influenced not only by the long-established scale effect, but also by a reallocation effect resulting from an increase in the relative size of more productive firms. We show how the relative importance of these effects, and hence the overall effect of trade liberalisation on the environment, is affected by the emission-intensity at the firm level: Aggregate emissions decrease when trade is liberalised if and only if firm-specific emission intensity decreases strongly with increasing firm productivity.
Keywords: F12; F18; Q56; 330; trade and environment; monopolistic competition; heterogeneous firms; environmental effects; Außenhandelsliberalisierung; Umweltbelastung; Monopolistischer Wettbewerb; Unternehmen; Produktivität; Theorie